Morinda officinalis polysaccharide improves osteoporosis by enhancing m⁶A-modified SOCS5 mRNA stability via regulating the hsa_circ_0001165/IGF2BP2 axis - ZhiBo Zhu; Yi Yang; Yi Liu; LingFeng Liao (Molecular Genetics and Genomics, 2026)

Largemouth bass virus infection subverts immune-redox homeostasis in zebrafish and is associated with coordinated suppression of NF-κB and Nrf2 signaling - Lingfeng Guan; Xinyue Zhang; Ting Yu; Yang Liu; Jiamei Long; Runchang Zhou; Hua Huang; Jinglin Tan; Zhifeng Chen; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2026)

Long-term bending performance degradation of GFRP bar-seawater sea sand concrete beams in marine environments: from material degradation to component response and bearing capacity model correction - Guanghao Mai; Zhe Xiong; Haoran Zhou; Lingfeng Zhou; Xiaohui Li; Feng Liu; Lijuan Li (Engineering Structures, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Substantial mitigation of nitrous oxide realized in a light-mediated and aeration-free microalgal-bacterial consortium system - Lingfeng Wang; Weican Shi; Yanlin Liu; Zhaoming He; Jianhua Guo; Shijian Ge; Shuang Qiu (Algal Research, 2026)

Integrating machine learning and deep learning with multiple molecular fingerprints for topoisomerase I inhibitor screening and lead identification - Huang Zeng; Xuerou Zheng; Jiayao Liu; Shengyuan Zhang; Hua Nie; Nan Wang; Lingfeng Wu; Chunfang Liu; Ming Zhai; Hao Yang; Jiunlong Yang; Bo Qiu (Molecular Diversity, 2026)

A one-stone-three-birds strategy: Manipulating sodiation depth of SnTe anode enabling fast ion conduction, shuttle avoidance, and sodium replenishment for durable sodium-ion batteries - Zhiming Jia; Guoping Liu; Xu Han; Gangyong Zhou; Haihui chen; Chunjiang Jin; Ting Liu; Lingfeng Xu; Renyun Kuang; Changwang Pan; Shengping Dai; Dingwa Zhang; et al. (Chemical Engineering Journal, 2026)

Strongly coordinating anions and cosolvent synergy enabled lithium metal batteries - Yutao Liu; Yi Li; LingFeng Zhang; Mengmeng Tan; QiXian Zhang; Wei Lü (Chemical Engineering Journal, 2026)

Interdigitated electric-magnetic gradient MXene-based nanocomposite films for concurrent high-efficiency electromagnetic shielding and sensitive detection - Lingfeng Yu; Yanni Yang; Shulong Chang; Yihao Xiao; Song Luo; Shichun Hao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Precursor-engineered lignin-derived Co/N-doped carbon for high-efficiency electrocatalytic HMF oxidation: The critical role of pretreatment history - Chenxin Jin; Yajun Liu; Lingfeng Li; Yihan Wang; Changzhou Chen; Jianchun Jiang (Biomass and Bioenergy, 2026)

Precipitation and shortwave radiation dominate vegetation recovery times from flash droughts across Köppen–Geiger climate zones - Lei Zou; Wenzhe Zhu; Jun Xia; Feiyu Wang; Dunxian She; Chengjian Liu; Jiayuan Xu; Lingfeng Zuo (Agricultural and Forest Meteorology, 2026)

A hydrodynamics-assisted remote sensing method for estimating vertical distribution of total suspended matter in lakes: a case study of Poyang Lake - Hui Jiang; Jiawei Ouyang; Yao Liu; Lingfeng Wan; Yungen Sun (Journal of Hydrology, 2026)

Effects of Salinity on Growth, Survival, Gonadal Development, and Immune-System Indicators of Crassostrea ariakensis - Xiaotong Li; Xue Zhang; Zhaoqi Liu; Lingfeng Kong (Journal of Ocean University of China, 2026)

Integrative multi-omics identifies CYP1B1 as a candidate molecular link between toxicant exposure and ferroptosis-related epithelial stress in COPD - Lingfeng Liu; Mingjun Jiang; Muzi Lei; Kun Du; Xiangyang Ye; Dafei Wei; Xiaowu Tan; Zhuang Mi; Yao Tang; Ruiting Sun; Sha Liu (Inflammation Research, 2026)

HMGB1 blockade attenuates cardiac injury induced by radiotherapy combined with PD-1 inhibitor while maintaining the anti-tumor efficacy - Yao Liu; Lingfeng Liu; Bibo Wu; Jing Zhang; Chaofen Zhao; Bing Lu; Yinxiang Hu; Weiwei Ouyang; Zhenneng Guo; Rong Hu; Shengfa Su (Apoptosis, 2026)

Nanoplastic exposure induces exoskeletal misdevelopment in juvenile Tachypleus tridentatus: Compensatory hardening versus molecular suppression - Lingfeng Jiang; Youji Wang; James Kar-Hei Fang; Khor Waiho; Wei Liu; Jae-Seong Lee; Xiaowan Ma; Menghong Hu (Marine Pollution Bulletin, 2026)

Dietary 5-aminolevulinic acid induces strain-specific effects on shell color and innate immunity in Pacific oyster (Crassostrea gigas) through divergent porphyrin metabolism - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Fish & Shellfish Immunology, 2026)

Partially etched Ti2AlN/Ti2N/TiN ternary composite as a synergistic catalyst for enhanced hydrogen storage kinetics and cycling stability of NaAlH4 - Chen Jin; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Development of a high-throughput sensitive SB-PCR assay for rapid detection of laboratory-escaped antibiotic resistance genes - Lingfeng Yan; Shengnan Liu; Rong Cao; Azadeh Nilghaz; Jiajin Wei; Hehui Long; Liming Zhang; Zhuoxuan Lu (Journal of Environmental Chemical Engineering, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Wheat density drives negative density dependence in nitrogen uptake and root plasticity in wheat–weed communities - Li Zhang; Weiqiang Liu; Yizhong Rong; Jiazhen Xi; Lingfeng Mao; Anna Gunina; Zhen Zhang (Rhizosphere, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Multifunctional polyvinyl alcohol composites via melt blending with a bio-based P-N synergistic flame retardant: Achieving simultaneous enhancement in fire safety, UV shielding, and mechanical properties - Junsheng Guo; Wenzong Xu; Tao Yan; Jiayan Zhang; Xiaoyu Guo; Lingfeng Wang; Julan Liu (Chemical Engineering Journal, 2026)

Synergistic CeH2.51/graphene nanointerface engineering for enhanced kinetics and cycling stability of Mg(NH2)2–2LiH - Chen Jin; Haoyuan Zheng; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

Multiscale-reinforced high-strength MXene-based EMI shielding films with integrated electronic skin functionalities - Lingfeng Yu; Yanni Yang; Xinyu Huang; Yihao Xiao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

The sea level rise of the 8.2 ka event simulated by the iCESM1.3 - Lingfeng Wan; Zhengyu Liu; Chengfei He; Chenyu Zhu; Shaoqing Zhang; Jiuyou Lu; Zhaowei Jing (Climate Dynamics, 2026)

Reproductive capacity and hereditary impact of triploid Crassostrea gigas and its aneuploid progeny - Xianchao Bai; Hong Hu; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Haijun Liu; Shaojun Du; Qi Li (Marine Life Science & Technology, 2026)

Orange-shell phenotype regulated by CgABCG2-mediated protoporphyrin IX transport in Pacific oyster (Crassostrea gigas) - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Aquaculture, 2026)

Parallel cooperative path following control for multiple cyber-physical MASSs based on DN-ESO - Lingfeng Li; Lu Liu; Bing Han; Bing Wu; Zhouhua Peng (Ocean Engineering, 2026)

Towards adaptive management: Future environmental risk assessment of tailing ponds in China under SSP scenarios - Junhong Ling; Bolun Zhang; Zhenxiong Zhao; Lingling Liu; Da Lv; Soon Thiam Khu; Lingfeng Zhou; Xiaoli Zhao (Journal of Environmental Management, 2026)

An incoherent feed-forward loop coordinates nitrate uptake and tillering in wheat - Weiya Xu; Yongming Chen; Yanxiao Niu; Bin Liu; Dejie Du; Xining Ning; Tong Huan; Yilan Zhou; Wensheng Ke; Lingfeng Miao; Weilong Guo; Mingming Xin; et al. (Molecular Plant, 2025)

Nanomaterial-powered immunotherapy: A next-generation therapeutic paradigm for bacterial infections - Xiaotong Sun; Shengnan Huang; Tong Ye; Lingfeng Xu; Yongfang Wang; Anqi Liu; Chao Liu; Yu Han; Mengfei Pang; Xuan Wu; Xin Pang (Chemical Engineering Journal, 2025)

Devonian–Triassic tectonic evolution of the Western Qinling Orogenic Belt of central China: Insights from detrital zircon U Pb chronology and rock geochemistry - Yan Zhang; Shuang Dai; Futian Liu; Dongbao Guo; Lingfeng Qin; Zhongzhao Ding; Yongfa Chen; Xinnan Fang; Xiaojun Ma; Yu Wang; Hua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Critical hydro-geomorphological characteristics related to lateral erosion–deposition difference within the multilevel bifurcation system of the Yangtze Estuary, China - Boyuan Zhu; Shiyu Zhang; Lingling Zhu; Lingfeng Liu; Wenjun Yu; Jinwu Tang; Yongzhou Cheng; Yitian Li; Alistair G.L. Borthwick (Journal of Hydrology, 2025)

Comparative analysis of machine learning based dissolved oxygen predictions in the Yellow River Basin: The role of diverse environmental predictors - Lingling Liu; Xiaoli Zhao; Lingfeng Zhou; Jiangtao Liu; Wenjing Li; Bolun Zhang; Junhong Ling; Fengchang Wu (Journal of Environmental Management, 2025)

Nano-magnetoelectric biomimetic system promotes neural differentiation and reverses dopaminergic neuron damage for Parkinson's disease therapy - Jie Zhang; Jiahui Shi; Qiubo Yang; Haogang Guo; Lingfeng Guo; Guoliang Zhou; Yinyi Liu; Xiaolei Wang; Xian Hao; Yifei Yang (Chemical Engineering Journal, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

A multiscale generative adversarial network approach for generating porous media with structural morphology - Yafei Xu; Lingfeng Guo; Danqing Song; Yi Shan; Xiaoli Liu (Stochastic Environmental Research and Risk Assessment, 2025)

Antarctic circumpolar current evolution and its relation to southern hemisphere westerly winds during the holocene - Lingfeng Wan; Dapeng Li; Chenyu Zhu; Zhengyu Liu; Shaoqing Zhang; Xiaopei Lin; Jiuyou Lu (Climate Dynamics, 2025)

Non-covalent bonding induced superior fire resistance of functionalized graphene oxide and carbon nanotubes paper for Joule heating and ultra-durable fire alarming - Ao Cai; Cunjiong Fang; Lingfeng Pan; Wenhua Chen; Pengju Liu; Hao Huang; Yuan Liu (Chemical Engineering Journal, 2025)

High-throughput screening and inhibition mechanism analysis of Bacillus licheniformis BL-4 as an antagonistic strain for Lactobacillus panis - Lingfeng Yi; Xinyue Li; Menglin She; Yaokang Wu; Jianghua Li; Guocheng Du; Long Liu; Li Wang; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2025)

Safety and Probiotics Evaluation of Bifidobacterial Genomes Isolated from Probiotic Products - Jue Li; Yinhuan Wang; Xingyu Xu; Xiaoling Zheng; Zhengnan Wang; Xiaofeng Chen; Lei Wang; Lingfeng Mao; Wangqin Ge; Huijun Liu; Wenwen Gao; Tingzhang Wang; et al. (Current Microbiology, 2025)

Adaptation of Marine Heterotrophic Protists to Long‐Term Warming Selection - Mengwen Pang; Zuyuan Gao; Lingfeng Huang; Chuk Man Chan; Xiaodong Zhang; Ruilin Su; Ke Pan; Hongbin Liu (Global Change Biology, 2025)
The rise in surface ocean temperature imposes strong effects on marine organisms. With large population sizes and fast generation times, microorganisms may rapidly adapt to ocean warming. However, long‐term experimental adaptation studies on heterotrophic protists are very limited, hindering our comprehensive understanding of their adaptation capability and the underlying mechanisms. In this study, we conducted long‐term thermal selection experiments on six representative marine protozoa. By assessing their phenotypes, metabolism, thermal performance curves, thermal traits, and carbon allocation status, we found that all investigated heterotrophic protists exhibited a fitness‐improved adaptation response to warming scenarios. After growing in warmer conditions for hundreds of generations (~850 for Cafeteria burkhardae and ~500 for other species), their optimal temperature and maximum rates of both growth and ingestion increased, whereas respiration rates significantly decreased. In addition, the cell size, cellular carbon, and nitrogen content at an elevated environmental temperature also increased after warming adaptation. Mechanisms underlying the increased competitive fitness at high temperatures after warming adaptation might be associated with the alleviated oxidative stress, shown by the remarkable reduction in cellular reactive oxygen species contents. Our study, for the first time, reveals the ability of marine heterotrophic protists to adapt to higher temperatures, providing experimental support for predictive modeling studies that integrate evolutionary potential with short‐term physiological responses, with important implications for marine ecosystem functioning and biogeochemical cycling under global warming.

Shell Colour Diversity in Marine Molluscs: From Current Knowledge to Future Aquaculture Applications - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Qi Li (Reviews in Aquaculture, 2025)
Mollusc shell colour represents an important economic trait contributing to product marketability in aquaculture. Marine molluscs with diverse shell colours and patterns are valuable models for animal colouration mechanisms study. Recent progress in marine mollusc shell colour research has been propelled by investigations of shell‐colour variants, advancements in high‐throughput sequencing technologies, and research into metabolic regulatory mechanisms for pigment biosynthesis. This review synthesizes current advancements in genetic architecture, gene regulatory networks and pigment metabolic processes governing shell colour variation in marine molluscs. In this review, insights gained from genetic studies uncover diverse inheritance patterns, key loci and present shell‐colour‐related transcriptomic datasets along with integrative multi‐omics studies. Moreover, distribution, metabolic networks and functional gene linkages of major pigments (melanin, carotenoids, and porphyrins) are characterized, while ommochromes are also discussed. Furthermore, environmental, dietary and structural factors influencing shell colour are listed. By synthesizing current findings, this review offers a detailed overview of the common factors influencing shell colour across marine mollusc species and probes the potential implications of shell colour studies for aquaculture. Future research directions emphasize pigment characterization, pigment transport mechanism studies and integrative multi‐omics approaches to bridge genetic and chemical understandings. In summary, this review outlines the current progress on marine mollusc shell colouration, provides referable research directions on shell‐colour‐related molluscs, and enhances understanding of animal colouration mechanisms.

Microplastics magnify inhibitive effects of perfluorooctanoic acid on the marine microbial loop - Peichun Lin; Xiaokun Liu; Zuyuan Gao; Yelinzi Yuan; Hongbin Liu; Lingfeng Huang; Zhili He; Qinglu Zeng; Shanquan Wang (Environmental Research, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Co-infection by RGNNV and V. rotiferianus in golden pompano: Insights into disease risks and immune responses - Xinshuai Li; Lingfeng Guan; Cuiyu Liu; Jinpeng Chen; Xin He; Yanwei Li; Shaowen Wang; Qiwei Qin; Min Yang (Aquaculture, 2025)

Review of Core-shell structure zeolite-based catalysts for NOx emission control - Lingfeng Jia; Jixing Liu; Huifang Cheng; Zhen Zhao; Jian Liu (Journal of Environmental Sciences, 2025)

Preparation of SCOF/UiO-66-NH2 immobilized laccase biocatalytic membrane for micropollutants removal from water - Tiantian Wang; Lingfeng Zhao; Guanhua Liu; Xiaoyang Yue; Xiaobing Zheng; Li Ma; Yunting Liu; Mimi Chen; Yanjun Jiang (Chemical Engineering Journal, 2025)

DOPA Decarboxylase (DDC) in Pacific Oysters: Characterization and Role in Tyrosine Metabolism and Melanogenesis - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

Advanced design of the crushing chamber for the sugarcane top silage cutter in harvester with experiments and simulation - Peng Huo; Shaochun Ma; Jun Qian; Weiqing Li; Baocheng Zhou; Wei Liu; Wenpeng Liang; Wenzhi Li; Changyu Wang; Sha Yang; Lingfeng Li; Yechen Li; et al. (Computers and Electronics in Agriculture, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Oral pH-Sensitive Solid Self-Microemulsion of Norcantharidin Wrapped in Colon-Coated Capsule for Selective Therapy of Colorectal Carcinoma - Xia Liu; Wenyou Fang; Wenjie Lu; Mingchao Xu; Zijun Wu; Dan Su; Lingzhen Ding; Qing Zhang; Jinguang Ouyang; Tianming Wang; Lingfeng Sun; Song Gao; et al. (AAPS PharmSciTech, 2025)

CgPPOX and CgFECH Mediate Protoporphyrin IX Accumulation Predominantly in the Outer Mantle Fold of Pacific Oyster Crassostrea gigas - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

DNA Methylation of Somatic Tissues in Oysters is Influenced by Sex and Heredity - Wen Teng; Chengxun Xu; Shikai Liu; Hong Yu; Lingfeng Kong; Qi Li (Marine Biotechnology, 2025)

Causes of Atypical Meiyu in the Lower Yangtze River Basin in 2022: Subseasonal Perspective and Predictions - Zhiqi Zhang; Ping Liang; Yajing Liu; Yang Wu; Lingfeng Tao; Qi Chen; Yihui Ding (Journal of Meteorological Research, 2025)

Examination of the roles of CgTH in tyrosine metabolism and pigmentation of Pacific oyster (Crassostrea gigas) - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Aquaculture, 2025)

Ion separation with graphene oxide nanofluidic membranes: A review - Dekang Pang; Lingfeng Liu; Xiaojing Zhang; Changsheng Guo; Jianbo Jia; Changyu Liu; Mengchen Zhang (Desalination, 2025)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

Network structure analysis based on embodied energy of the Australian economy - Lingfeng Liang; Yabing Xu; Bin Liu; Chunlu Liu; Youquan Xu; Mark Luther (Journal of Cleaner Production, 2024)

The influence of digestive tract protein on cytotoxicity of polyvinyl chloride microplastics - Gonghao Liu; Qianwen Jiang; Lingfeng Qin; Zihang Zeng; Peng Zhang; Bo Feng; Xiaofeng Liu; Zhihe Qing; Taiping Qing (Science of The Total Environment, 2024)

Janus graphene oxide membrane with rational allocation of functional regions as unidirectional ion valve system - Jundong Yan; Lingfeng Liu; Zhichen Liang; Chongfeng Huang; Wenbiao Zheng; Changsheng Guo; Minchao Liu; Chao Peng; Jianbo Jia; Mengchen Zhang (Desalination, 2024)

Characterization of piRNAs in Diploid and Triploid Pacific Oyster Gonads: Exploring Their Potential Roles in Triploid Sterility - Yaru Zhou; Hong Yu; Qi Li; Lingfeng Kong; Shikai Liu; Chengxun Xu (Marine Biotechnology, 2024)

Unveiling the structure-performance of MoO3/La2O2CO3 for ultra-deep aerobic oxidative desulfurization of diesel - Shijia Shao; Hui Liu; Xiangdong Wang; Lingfeng Jia; Shuhui Zhou; Yan Huang; Huifang Cheng; Feng Liu; Yun Wang; Jixing Liu; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Comparative analysis on growth performance, survival and harvest traits between offspring from wild and mass-selected populations of Crassostrea nippona - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Aquaculture, 2024)

Comparison of the toxic effects of polystyrene and sulfonated polystyrene on wheat under cadmium stress - Lingfeng Qin; Gonghao Liu; Jiaoyan Huang; Zihang Zeng; Ya Zeng; Taiping Qing; Peng Zhang; Bo Feng (Journal of Hazardous Materials, 2024)

OysterDB: A Genome Database for Ostreidae - Xinchun Li; Yitian Bai; Chengxun Xu; Shikai Liu; Hong Yu; Lingfeng Kong; Shaojun Du; Qi Li (Marine Biotechnology, 2024)

FSP1-mediated ferroptosis in cancer: from mechanisms to therapeutic applications - Ran Gao; Jinge Wang; Jingjing Huang; Tong Wang; Lingfeng Guo; Wenlu Liu; Jialu Guan; Desen Liang; Qinghui Meng; Huayang Pan (Apoptosis, 2024)

Examination of the effects of impaired spermatogenesis on sterility in triploid oysters (Crassostrea gigas), and implications for commercial aquaculture - Chen Chen; Hong Yu; Qi Li; Lingfeng Kong; Shikai Liu; Chengxun Xu (Aquaculture, 2024)

Hypoxia impairs cellular energy allocation in the juvenile horseshoe crab Tachypleus tridentatus - Lingfeng Jiang; Meilian Huang; Chunhua Liu; Mohamed H. Abo-Raya; Xiaowan Ma; Youji Wang; Menghong Hu (Journal of Experimental Marine Biology and Ecology, 2024)

Recent advances on environmental behavior of Cu-based nanomaterials in soil-plant system: A review - Jieyu Gao; Yi Zhu; Lingfeng Zeng; Xin Liu; Yuan Yang; Yaoyu Zhou (Journal of Environmental Management, 2024)

Modulating the acidity and reducibility of FeMn/TiO2 to boost the low-temperature selective catalytic reduction of NOx - Jingyi Zhu; Yuankai Shao; Zhenguo Li; Kaixiang Li; Xiaoning Ren; Lingfeng Jia; Huiquan Li; Huifang Cheng; Jian Liu; Jixing Liu (Fuel, 2024)

cAMP-Mediated CREM-MITF-TYR Axis Regulates Melanin Synthesis in Pacific Oysters - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Relationship between eutrophication and greenhouse gases emission in shallow freshwater lakes - Jingjie Zhang; Lingfeng Cao; Zhenghan Liu; Lingling Wan; Xiuyun Cao; Yiyong Zhou; Chunlei Song (Science of The Total Environment, 2024)

Experimental and modeling study of ignition delay times of n-C5H12 and C3H6 under O2/CO2 atmospheres - Chao Peng; Chun Zou; Jiaxin Ren; Qianjin Lin; Wenxiang Xia; Lingfeng Dai; Jiacheng Liu; Wenyu Li (Fuel, 2024)

Current progress on manganese in constructed wetlands: Bibliometrics, effects on wastewater treatment, and plant uptake - Lingfeng Zeng; Xin Liu; Jiezhi Ma; Jie Yang; Jian Yang; Yaoyu Zhou (Environmental Research, 2024)

Differences in the activities of six soil enzymes in response to cadmium contamination of paddy soils in high geological background areas - Juan Liu; Xinyang Li; Qilin Zhu; Jiawen Zhou; Lingfeng Shi; Weihong Lu; Li Bao; Lei Meng; Longhua Wu; Naiming Zhang; Peter Christie (Environmental Pollution, 2024)

Transcriptomic and Physiological Analysis Reveal Melanin Synthesis-Related Genes and Pathways in Pacific Oysters (Crassostrea gigas) - Kunyin Jiang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Potential mobilization of water-dispersible colloidal thallium and arsenic in contaminated soils and sediments in mining areas of southwest China - Yanpei Du; Lingfeng Shi; Xinyang Li; Juan Liu; Rongrong Ying; Pengjie Hu; Longhua Wu; Peter Christie (Journal of Hazardous Materials, 2024)

Genetic improvement of oysters: Current status, challenges, and prospects - Kunyin Jiang; Chen Chen; Gaowei Jiang; Yong Chi; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Reviews in Aquaculture, 2024)
Oysters are one of the most commercially important shellfish species and have been cultured for thousands of years. Oyster aquaculture supports the major aquaculture industries in many countries. Over the last few decades, the oyster breeding and aquaculture industries have developed rapidly to meet the continually growing demand. Many researchers have made significant efforts toward the genetic improvement of commercially important traits in oysters. Some strains with fast‐growing, disease‐resistant, and stable shell‐colours have been developed through selective breeding. Some hybrid varieties have been developed by crossing different geographical populations or cultivated strains. Several hybrids exhibit considerable genetic variation and improved productive performance. Additionally, polyploid induction technologies have been applied in the oyster aquaculture industry, which provides a useful tool for performance improvement and genetic containment of cultured stocks. At present, the development of molecular breeding also provides a great opportunity for oyster genetic improvement. These advances in oyster breeding have improved the quality of oysters, brought great economic benefits, and been conducive to the sustainability of oyster production. Nonetheless, there are still some limitations and obstacles in oyster breeding, such as infectious diseases, summer mortality, conservation of germplasm resources, environmental contamination, and climate change. The present review provides an overview of the current status, challenges, and prospects in oyster breeding.

Effects of cadmium exposure during pregnancy on genome-wide DNA methylation and the CREB/CREM pathway in the testes of male offspring rats - Xiushuai Du; Jianlin Zhu; Xueming Xu; Zhilan Lu; Xiaoqin Li; Yuchen Li; Lingfeng Luo; Wenchang Zhang; Jin Liu (Chemosphere, 2024)

Exposure, bioaccumulation, and risk assessment of organophosphate flame retardants in crayfish in the middle and lower reaches of the Yangtze River - Qiuhong Peng; Lingfeng Peng; Jin Liu; Yan Liu; Xin Liu; Jiaojiao Yin; Shuo Duan; Xiaofang Liu; Yuzhi Li; Zhiyong Gong; Qiao Wang (Science of The Total Environment, 2024)

Water-dispersible colloids facilitate the release of potentially toxic elements from contaminated soil under simulated long-term acid rain - Juan Liu; Lingfeng Shi; Yanpei Du; Xueting Luo; Pengjie Hu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Stable oganocopper(III) complexes generated via oxidative addition - Lingfeng Yin; Wei Liu (Science Bulletin, 2024)

Numerical investigation on the spray characteristics of biodiesel with gas-assisted atomization injection - Rui Liu; Lingfeng Zhong; Songhong Li; Jing Li; Haocheng Ji (Fuel, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Taxonomy and distribution of three species of Barleeia (Mollusca, Gastropoda, Littorinimorpha, Barleeiidae) in the intertidal zone off the coast of China, with description of a new species, Barleeia qilu Han, Qi & Kong, n. sp. - Xiao Han; Biyang Xu; Lu Qi; Shiyuan Liu; Lingfeng Kong (Molluscan Research, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

A low-carbon CO2 ice rink technology for the Winter Olympics - Ligeng Li; Kai Liu; Hua Tian; Jinwen Cai; Christos N Markides; Jingyu Wang; Lingfeng Shi; Xuan Wang; Yitai Ma; Xingyu Liang; Gequn Shu (Science Bulletin, 2023)

Ecological utility analysis of the Australian economic sectors based on embodied energy - Lingfeng Liang; Yabing Xu; Bin Liu; Chunlu Liu; Youquan Xu; Mark Luther (Journal of Cleaner Production, 2023)

Contraction of Heat Shock Protein 70 Genes Uncovers Heat Adaptability of Ostrea denselamellosa - Zhen Dong; Shikai Liu; Hong Yu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2023)

Experimental studies on active oxygen control performance of solid PbO mass exchanger in liquid lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Zhenhua Sheng; Xiaobo Li; Muran Qi; Yifeng Wang; Lingfeng Yang; Xu Tu; Hao Wu; Fang Liu; Zhangpeng Guo; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Future changes in hydrological drought across the Yangtze River Basin: identification, spatial–temporal characteristics, and concurrent probability - Jiarui Yu; Lei Zou; Jun Xia; Ming Dou; Huan Liu; Lingfeng Zuo (Journal of Hydrology, 2023)

Parallel evolution in Crassostrea oysters along the latitudinal gradient is associated with variation in multiple genes involved in adipogenesis - Wen Teng; Huiru Fu; Zhuanzhuan Li; Qian Zhang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Molecular Ecology, 2023)
Parallel diversification provides a proper framework for studying the role of natural selection in evolution. Yet, empirical studies from ecological ‘non‐model’ species of invertebrates are limited at the whole genome level. Here, we presented a chromosome‐scale genome assembly for Crassostrea angulata and investigated the parallel genomic evolution in oysters. Specifically, we used population genomics approaches to compare two southern–northern oyster species pairs ( C . angulata – C . gigas and southern–northern C . ariakensis ) along the coast of China. The estimated divergence time of C . angulata and C . gigas is earlier than that of southern and northern C . ariakensis , which aligns with the overall elevated genome‐wide divergence. However, the southern–northern C . ariakensis F ST profile represented more extremely divergent “islands”. Combined with recent reciprocal hybridization studies, we proposed that they are currently at an early stage of speciation. These two southern–northern oyster species pairs exhibited significant repeatability in patterns of genome‐wide differentiation, especially in genomic regions with extremely high and low divergence. This suggested that divergent and purifying selection has contributed to the genomic parallelism between southern and northern latitudes. Top differentiated genomic regions shared in these two oyster species pairs contained candidate genes enriched for functions in energy metabolism, especially adipogenesis, which are closely related to reproductive behaviours. These genes might be good candidates for further investigation in vivo. In conclusion, our results suggest that similar divergent selection and shared genomic features could predictably transform standing genetic variation within one species pair into differences in another.

Solvent effect to modulate nitrogen dopant in Co-N-C catalysts for oxygen reduction reaction acceleration - Lingfeng Li; Guokang Han; Yandi Wen; Yuxin Liu; Rang Xiao; Wei Zhang; Fanpeng Kong; Lei Du; Yulin Ma; Pengjian Zuo; Chunyu Du; Geping Yin (Fuel, 2023)

Construction of hybridization chain reaction induced optical signal directed change of photonic crystals-DNA hydrogel sensor and its visual determination for aflatoxin B1 - Qianshan Chen; Lingfeng Wu; Feng Zhao; Bing Liu; Zhaoyang Wu; Ruqin Yu (Food Chemistry, 2023)

Effects of Dietary Cystine and Tyrosine Supplementation on Melanin Synthesis in the Pacific Oyster (Crassostrea gigas) - Zhuanzhuan Li; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Surface display of major capsid protein on Bacillus subtilis spores against largemouth bass virus (LMBV) for oral administration - Quan Wang; Xia Liang; Yunshang Ning; Shijia Liu; Zengjian Liang; Zemiao Zhang; Yingjing Chen; Jinqiao Cao; Fubao Wang; Lingfeng Lan; Guangzhao Cheng; Youhua Huang; et al. (Fish & Shellfish Immunology, 2023)

Paternal genetic intergenerational and transgenerational effects of cadmium exposure on hormone synthesis disorders in progeny ovarian granulosa cells - Yi Sun; Chenyun Zhang; Lingfeng Luo; Hao Lin; Chenchen Liu; Wenchang Zhang (Environmental Pollution, 2023)

Transcriptome Analysis of Reciprocal Hybrids Between Crassostrea gigas and C. angulata Reveals the Potential Mechanisms Underlying Thermo-Resistant Heterosis - Gaowei Jiang; Yin Li; Geng Cheng; Kunyin Jiang; Jianmin Zhou; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Degradation of PAHs in soil by activated persulfate system with activated carbon supported iron-based bimetal - Congcong Zhang; Huifang Tian; Zhaoxu Wang; Lingfeng Zhu; Xingshuang Liu; Ye Wang; Yifei Sun (Science of The Total Environment, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

A Comparative Study on the Difference in Temperature and Salinity Tolerance of Crassostrea nippona and C. gigas Spat - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Journal of Marine Science and Engineering, 2023)
Although Crassostrea nippona and C. gigas are occasionally found to be sympatric, little is known about the differences in tolerance against environmental stresses between species, which may potentially result in severe economic losses due to the neglect of species-specific biological characteristics in farming practices. Therefore, two independent and consecutive experiments were performed to evaluate the differences in temperature and salinity tolerance between C. nippona and C. gigas spat and determine the optimal environmental conditions for the aquaculture of C. nippona spat. The experimental results of dynamic treatment showed that the accumulative survival rate (ASR) of C. nippona spat was generally lower than that of C. gigas throughout temperature changes and salinity decreases, while the ASR of C. nippona spat was superior to that of C. gigas with increasing salinity. In addition, the daily growth rate (DGR) of both species was significantly inhibited at 18 °C and peaked at 25 °C with increasing temperature (p

Water mass-driven multiple ecological effects determine the biodiversity and community assembly of microbial flagellates in subtropic-tropic marginal seas of China - Xin Guo; Qiang Liu; Xiaoqing Lin; Xinyi Zheng; Cheng Huang; Mengwen Pang; Lingfeng Huang (Estuarine, Coastal and Shelf Science, 2023)

Interaction among soil nutrients, plant diversity and hypogeal fungal trophic guild modifies root-associated fungal diversity in coniferous forests of Chinese Southern Himalayas - Nan Yang; Yan Zhang; Jingji Li; Xiuxiu Li; Honghua Ruan; Parag Bhople; Katharina Keiblinger; Lingfeng Mao; Dong Liu (Plant and Soil, 2022)

Identification of ferroptosis-related signature with potential implications in prognosis and immunotherapy of renal cell carcinoma - Lingfeng Liu; Huan Jin; Mengyuan Dong; Jingwen Tian; Hongsheng Li; Quentin Liu; Yibing Chen; Zhengzhi Zou (Apoptosis, 2022)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

Shell Biosynthesis and Pigmentation as Revealed by the Expression of Tyrosinase and Tyrosinase-like Protein Genes in Pacific Oyster (Crassostrea gigas) with Different Shell Colors - Yijing Zhu; Qi Li; Hong Yu; Shikai Liu; Lingfeng Kong (Marine Biotechnology, 2021)

Faster recovery of soil biodiversity in native species mixture than in Eucalyptus monoculture after 60 years afforestation in tropical degraded coastal terraces - Wenjia Wu; Luhui Kuang; Yue Li; Lingfeng He; Zhijian Mou; Faming Wang; Jing Zhang; Jun Wang; Zhi’an Li; Hans Lambers; Jordi Sardans; Josep Peñuelas; et al. (Global Change Biology, 2021)
Afforestation is an effective method to restore degraded land. Afforestation methods vary in their effects on ecosystem multifunctionality, but their effects on soil biodiversity have been largely overlooked. Here, we mapped the biodiversity and functioning of multiple soil organism groups resulting from diverse afforestation methods in tropical coastal terraces. Sixty years after afforestation from bare land (BL), plant species richness and the abundance of plant litter (398 ± 85 g m −2 ) and plant biomass (179 ± 3.7 t ha −1 ) in native tree species mixtures (MF) were restored to the level of native forests (NF; 287 ± 21 g m −2 and 243.0 ± 33 t ha −1 , respectively), while Eucalyptus monoculture (EP) only successfully restored the litter mass (388 ± 43 g m −2 ) to the level of NF. Soil fertility in EP and MF was increased but remained lower than in NF. For example, soil nitrogen and phosphorus concentrations in MF (1.2 ± 0.2 g kg −1 and 408 ± 49 mg kg −1 , respectively; p −1 and 523 ± 24 mg kg −1 , respectively; p

Study on bioleaching of heavy metals and resource potential from tannery yard sludge - Hang Liu; Kaizhi Yang; Lingfeng Luo; Qian Lu; Yonggui Wu; Meiyan Lan; Youfa Luo; Wan Liang (Environmental Science and Pollution Research, 2021)

Integrated Analysis of Coding Genes and Non-coding RNAs Associated with Shell Color in the Pacific Oyster (Crassostrea gigas) - Zhuanzhuan Li; Qi Li; Shikai Liu; Ziqiang Han; Lingfeng Kong; Hong Yu (Marine Biotechnology, 2021)

Phylogeny of Veneridae (Bivalvia) based on mitochondrial genomes - Yu Wang; Yi Yang; Hongyue Liu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Zoologica Scripta, 2021)
Veneridae is one of the most diverse families of bivalve molluscs. However, their phylogenetic relationships among subfamilies have been debated for years. To explore phylogenetic relationships of Veneridae, we sequenced 13 complete mitochondrial genome sequences from eight subfamilies and compared with available complete mitochondrial genome of other Veneridae taxa (18 previously reported sequences). Phylogenetic analyses using probabilistic methods recovered two highly supported clades. In addition, the protein‐coding gene order revealed a highly conserved pattern among the same subclade lineages. According to our molecular analyses, Tapetinae should be recognized as a valid subfamily, but the genera formed para‐polyphyletic clades. Chioninae was recovered not monophyletic that differs from a previously molecular phylogeny. Furthermore, the reconstructed chronogram calibrated with fossils recovered the Veneridae have originated during the early Permian (about 290 million years ago). Noticeably, programmed frameshift was found in the nad4 gene of Leukoma jedoensis , Anomalodiscus squamosus and Antigona lamellaris and cob gene of L. jedoensis . This is the first time that the presence of the programmed frameshift has been found in the protein‐coding genes of Heterodonta species. Our results improved the phylogenetic resolution within Veneridae, and a more taxonomic sampling analysis of the subfamily Chioninae is supposed to construct.

Mitogenomic phylogeny of Trochoidea (Gastropoda: Vetigastropoda): New insights from increased complete genomes - Erfei Guo; Yi Yang; Lingfeng Kong; Hong Yu; Shikai Liu; Zhanjiang Liu; Qi Li (Zoologica Scripta, 2021)
Increased mitochondrial (mt) genomes can provide more sets of genome‐level characteristics for resolving deeper phylogeny. Limited information with respect to the Trochoidea mitochondrial genome organization is available; besides, monophyly and internal relationships of the superfamily still remain a matter of discussion. To resolve the monophyly and internal phylogenetic controversies of Trochoidea and expand our understanding for mt genomic characteristic evolution among Trochoidea, the phylogenetic trees were reconstructed using 13 newly sequenced complete mt genomes and 35 genomes from GenBank, and both the maximum likelihood and Bayesian inference analyses were highly supported. Vetigastropoda phylogenetic analyses recovered the monophyly of Trochoidea. Trochoidea phylogenetic analyses and genetic distances supported the non‐monophyly of Tegulidae and Tegula , indicating that the taxonomic status of several genera ( Rochia , Tectus and Cittarium ) should be revised and Tegula , Omphalius and Chlorostoma should be placed as a same genus. The close affinity between Tectus virgatus and Rochia was also revealed. Three‐nucleotide insertion in nad1 , nine‐nucleotide insertion and six‐nucleotide deletion in nad5 are detected in Tegulidae, Tectus and Rochia , respectively. Gene orders within Trochoidea are stable, with gene rearrangements exclusive to tRNA genes observed. Homoplasious convergences because of trnT rearrangement display translocation in Turbinidae and reversion in Trochidae and Calliostomatida. For trnE and trnG , we identify 11 arrangement types, suggesting that the gene rearrangement history needs to be further evaluated. Our study emphasizes the importance of mt genomes in resolving phylogenetic relationships within Trochoidea. In addition, the mt genomic characters would contribute new insights into the classification of Trochoidea.

Validation of Housekeeping Genes for Gene Expression Analysis in Iwagaki Oyster (Crassostrea nippona) Under Salinity Stress by Quantitative Real-Time PCR - Jianwen Gong; Qi Li; Hong Yu; Shikai Liu; Lingfeng Kong (Journal of Ocean University of China, 2020)

Mitogenomic phylogeny of the Naticidae (Gastropoda: Littorinimorpha) reveals monophyly of the Polinicinae - Hongyue Liu; Yi Yang; Shao'e Sun; Lingfeng Kong; Qi Li (Zoologica Scripta, 2020)
The Naticidae is a species‐rich family of predatory marine gastropods with substantial interspecific morphological diversity. The classification of the Naticidae has been traditionally based on morphology data, but the phylogenetic relationships within the family are debated due to conflicting molecular results, especially regarding the monophyly of subfamilies Polinicinae and Naticinae. To further resolve the phylogenetic controversies within the Naticidae, we undertake a phylogenetic approach using 14 newly sequenced complete or nearly complete (only lacking a control region) mitochondrial genomes. Both the maximum likelihood and Bayesian inference analyses supported monophyly of the Polinicinae, but paraphyly of the Naticinae due to the placement of the enigmatic genus Notocochlis . The ancestral character reconstruction suggests that the operculum, a character that currently defines the two subfamilies, evolved from an ancestor with a calcareous operculum in the evolutionary history of naticids. In addition, the chronogram estimates that naticids was originated in late Triassic (about 227 million years ago), consistent with previous hypotheses. Our study highlights the importance of using complete mitochondrial genomes while reconstructing phylogenetic relationships within the Naticidae. The evolution scenario of the naticid operculum contributes new insights into the classification of Naticidae.

Three-Dimensional Fluid–Solid Coupling Numerical Simulation of Effects of Underlying Karst Cave on Shield Tunnel Through Sand Stratum - Wei Wang; Shiming Gao; Youwei Min; Lingfeng Liu; Jianping Chen (Geotechnical and Geological Engineering, 2019)

Mass Selection for Growth Improvement in Black Shell Line of Pacific Oyster Crassostrea gigas - Chengxun Xu; Qi Li; Jindou Chong; Shikai Liu; Lingfeng Kong (Journal of Ocean University of China, 2019)

Fertilization, survival and growth of hybrids between Crassostrea gigas and Crassostrea sikamea - Hongqiang Xu; Qi Li; Lingfeng Kong; Hong Yu; Shikai Liu (Fisheries Science, 2019)

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

Performance of the BDS3 experimental satellite passive hydrogen maser - Ziqian Wu; Shanshi Zhou; Xiaogong Hu; Li Liu; Tao Shuai; Yonghui Xie; Chengpan Tang; Junyang Pan; Lingfeng Zhu; Zhiqiao Chang (GPS Solutions, 2018)

Comparison of microsatellites and SNPs for pedigree analysis in the Pacific oyster Crassostrea gigas - Ting Liu; Qi Li; Lingfeng Kong; Hong Yu (Aquaculture International, 2017)

Relationship between single nucleotide polymorphism of glycogen synthase gene of Pacific oyster Crassostrea gigas and its glycogen content - Siwei Liu; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2017)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Genetic variation and population structure of the Pacific oyster Crassostrea gigas in the northwestern Pacific inferred from mitochondrial COI sequences - Shuang Li; Qi Li; Hong Yu; Lingfeng Kong; Shikai Liu (Fisheries Science, 2015)

Reproductive cycle and seasonal variations in lipid content and fatty acid composition in gonad of the cockle Fulvia mutica in relation to temperature and food - Wenguang Liu; Qi Li; Lingfeng Kong (Journal of Ocean University of China, 2013)

Isolation and characterization of 14 microsatellite loci in Macridiscus semicancellata (Koch in Philippi, 1843) - Xinyu Liu; Lingfeng Kong; Hong Yu; Qi Li (Conservation Genetics Resources, 2013)

Selection response and realized heritability for growth in three stocks of the Pacific oyster Crassostrea gigas - Qi Li; Qingzhi Wang; Shikai Liu; Lingfeng Kong (Fisheries Science, 2011)

Effect of starvation on biochemical composition and gametogenesis in the Pacific oyster Crassostrea gigas - Wenguang Liu; Qi Li; Fengxiang Gao; Lingfeng Kong (Fisheries Science, 2010)

Seasonal changes in reproductive activity and biochemical composition of the razor clam Sinonovacula constricta (Lamarck 1818) - Hongwei Yan; Qi Li; Wenguang Liu; Ruihai Yu; Lingfeng Kong (Marine Biology Research, 2010)

Estradiol‐17β and testosterone levels in the cockle Fulvia mutica during the annual reproductive cycle - Wenguang Liu; Qi Li; Lingfeng Kong (New Zealand Journal of Marine and Freshwater Research, 2008)
In this study, we investigated seasonal variations in the concentrations of estradiol‐17β (E 2 ) and testosterone (T) in the gonad of the cockle Fulvia mutica from March 2004 to February 2005 in relation to the reproductive cycle. Histological data showed that F. mutica is a hermaphrodite bivalve species, and gametogenesis took place during winter‐spring (November‐April) and spawning occurred in summer (May‐June) when water temperature was higher. E 2 and T concentrations were measured by enzyme‐linked immunosorbent assay (ELISA). E 2 concentrations varied between 7.27 and 32.63 pg/g wet weight and T concentrations ranged from 22.83 to 77.15 pg/g wet weight throughout the year. Both steroids exhibited a similar annual pattern that correlated with the reproductive cycle. The two peaks of E 2 and T concentrations in November and May‐June occurred at critical moments of the F mutica reproductive cycle: the onsets of gametogenesis and of the spawning period. E 2 andT concentrations were low during the non‐reproductive period extending from July to October. These results suggest that E 2 and T could play a role as endogenous modulators in the reproductive cycle of F. mutica .

Cloning and Characterization of a Novel Human Prefoldin and SPEC Domain Protein Gene (PFD6L) From the Fetal Brain - Jiayi Zhang; Lingfeng Liu; Xiaomeng Zhang; Feng Jin; Jinzhong Chen; Chaoneng Ji; Shaohua Gu; Yi Xie; Yumin Mao (Biochemical Genetics, 2006)

Molecular cloning and characterization of a novel human protein phosphatase 2C cDNA (PP2C ε) - Feng Jin; Chaoneng Ji; Lingfeng Liu; Jianfeng Dai; Shaohua Gu; Xianfei Sun; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)